Design of an Application to Calculate Student Grades in Learning Logic Informatics Propositional Calculus Material - Al-Khowarizmi Al-Khowarizmi; Asrar Aspia Manurung; Mulkan Azhari (Ilmu Bersama Center, 2023)
Propositional calculus is a method used to calculate the truth value of a proposition. Propositional calculus is commonly studied by various students, from high school to college. Propositional calculus studies the truth value (True/False) of a proposition. The proposition is then processed into the steps of working on the proposition according to the order of operator priority, which is packaged into truth tables and logical expressions. The proposition work done is not easy, but consumes a lot of time and writing media if done manually. Errors in doing proposition work result in inaccurate truth values obtained. Therefore, the author is interested in making an application to calculate student grades using the propositional calculus method that can be used to overcome the problem of working on propositions manually, so that it can produce accurate truth values, which can also be used as a learning medium and media for students to calculate and see the results of their grades manually.